DIMENSION 6 BIM IMPLEMENTATION (SUSTAINABILITY & EFFICIENCY) IN THE PROCUREMENT PROCUREMENT CYCLE GOODS & SERVICES - Arnoldus Jean Cornelis (International Journal Labs, 2022)
The application of the Building Information Model (BIM) method in a construction project, especially in Indonesia, can be counted as few who have implemented it in aligning the planning and implementation of a construction project activity, while if there is an application of the BIM concept, most of it is only as a formality only on the completeness of the Form document. of course, where the reality is that in practice there are many procedural deviations in creating an